Bioethanol Production from Presto Pretreatment of Sorghum Stem by Simultaneous Saccharification and Cofermentation Technique and Purification Using Ende Natural Zeolites - Jasman, Jasman; Sarifudin, Kasimir (Jurnal Beta Kimia, 2024)
One form of new renewable energy source with promising prospects in dry climate areas is bioethanol produced from sweet sorghum. In this research, bioethanol was produced from sweet sorghum stem pulp, which had been treated by boiling in a pressure cooker (presto) for varying times. The fermentation technique used is Simultaneous Saccharification and Cofermentation (SSCF) using a mixed culture of Trichoderma reesei-Saccharomyces cerevisiae. Next, the bioethanol is purified using adsorbent made from Ende natural zeolite. The results showed that press-cooked sweet sorghum stalk pulp produced less ethanol than non-press-cooked sorghum pulp. The longer the pressure treatment time, the less ethanol produced. Throughout the three adsorption stages, the physically activated-Zeolite (only calcined at 600 °C for 3 h) increased the ethanol concentration from 94% to 99%. Zeolites activated with acid (HCl) can increase the ethanol concentration from 94% to 96%, while those activated with bases (NaOH 4M) can increase the ethanol concentration from 94% to 95.5%.